Psychometric properties of the Aggression Questionnaire (AQ) in university students - Espinoza, Ingrid; Tobar Viera, Andrea (Revista Ecos de la Academia, 2023)
Aggression is a predisposing factor for violence, it encompasses negative attitudes such as anger and hostility, and can be presented verbally and physically with the intention of hurting others. It occurs in adolescent age groups and in the university youth population. In addition, it is necessary to emphasize the absence of reliable psychometric instruments for the evaluation of this variable in the Ecuadorian context. A psychometric instrumental methodology was used to determine the psychometric properties of the Aggression Questionnaire (AQ), with the participation of 632 university students from Ecuador, 64.4% of whom were female and 35.6% male, with a mean age of 20.5.  The results showed an adequate adjustment in the three-factor model and an optimum reliability with a Cronbach's Alpha of 0.92. Likewise, the mean score was determined according to sex, resulting in a significant presence of aggression in the male gender. It was concluded that the research presents adequate consistency and reliability, which indicates that the instrument can be used with caution in the university population.
Keywords: Aggression; Psychometrics; Questionnaires; University students; Violence